GAME-BASED LEARNING DESIGN FOR INTEGER OPERATIONS USING DOJUKU TO ENHANCE MATHEMATICAL REPRESENTATION AND INTEREST - Rahmawati, Ajeng Hilda; Saputra, , Samnur; Robiansyah, Endi (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2025)
Mathematics is a compulsory subject from elementary to high school levels. However, many junior high school students still find it difficult, especially in integer operations, because they are abstract. One of the causes is the low representational abilities and learning interest of students. To overcome this problem, innovation in learning is needed. Observations in class VII of junior high school in West Java show that students really like games. This research used Formative Evaluation (Tessmer, 1993) with subjects of 30 students, educators and mathematics education experts. Research instruments include expert validation sheets, evaluation tests, questionnaires and interviews. This research aims to determine validation, mathematical representation abilities, and students' interest in learning through the game-based learning media Domino Jumlah Kurang (DoJuKu). The results of the analysis show that DoJuKu can facilitate students' mathematical representation abilities and learning interest in the high category.